Analyzing experimental music performance in "AquaSonic" by Between Music - Robi Rusdiana; Shivani Ramadhanty (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2022)
This essay analyzes the performance of experimental music in Between Music’s Aquasonic Project using a qualitative approach. We investigate the creative combination of music and underwater performance art by analyzing various sources such as literature and audio-visual information found on platforms like YouTube. The essay explores the distinctive difficulties and artistic opportunities that arise from performing music underwater, focusing specifically on Between Music’s Aquasonic Project. The project explores the ways in which it challenges the conventional norms of music performance by combining avant-garde music, visual arts, and scientific investigation. The study reveals the complex and diverse aspects of the Aquasonic Project, emphasizing its dependence on specialized instruments, the acoustic characteristics of water, and the physical interactions between the performers and their underwater surroundings. The essay offers a detailed analysis of the experimental music performance landscape in the Aquasonic Project by combining insights from study literature and analysis video on YouTube. It highlights need to work together across several disciplines, using advanced technology and exploring new artistic ideas to expand the limits of musical expression. Moreover, the study proposes possible areas for future investigation and artistic development in the field of underwater music performance, highlighting its capacity to evoke wonder, stimulate contemplation, and alter traditional concepts of musical engagement.